Enterocytozoon bieneusi in Minks (Neovison vison) in Northern China: A Public Health Concern - Zhang, Xiao-Xuan; Jiang, Ruo-Lan; Ma, Jian-Gang; Xu, Chao; Zhao, Quan; Hou, Guangyu; Liu, Guo-Hua (Frontiers in Microbiology, 2018)
Enterocytozoon bieneusi is the most important causative agent of microsporidiosis and can infect almost all vertebrate and invertebrate hosts, including minks (Neovison vison). In the present study, a total of 298 feces samples (including 79 from Heilongjiang province, 31 from Hebei province, 67 from Jilin province, 90 from Liaoning province and 31 from Shandong province, Northern China) were examined by nested PCR amplification of the internal transcribed spacer (ITS) region of the rRNA gene. The overall prevalence of E. bieneusi in minks was 10.1%, with 10.5% in Jilin province, 32.3% in Hebei province, 8.9% in Liaoning province, 0% in Shandong province, and 6.3% in Heilongjiang province. Furthermore, multiple logistic regression analysis revealed that region was only risk factors associated with E. bieneusi infection in the investigated minks. Five E. bieneusi ITS genotypes (three known genotypes, namely D, Peru11, and EbpC; two novel genotypes, namely, NCM-1 and NCM-2) were found in the current study. Importantly, genotypes D, Peru11 and EbpC, previously identified in humans, were also found in minks, which suggested that minks are the potential sources of human microsporidiosis. To the best of our knowledge, this is the first report of E. bieneusi infection in minks worldwide. The results of the present survey have implications for the controlling E. bieneusi infection in minks, other animals and humans.